Pengaruh Aplikasi Dosis NPK Ponska terhadap Kehilangan Hasil Bawang Merah (Allium ascalonicum L.) Akibat Kompetisi Gulma di Lahan Kering - I Ketut Ngawit; Bambang Budi Santoso; Jayaputra Jayaputra (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
It is not yet known, among the nutsedge, grasses, and broad-leaved plants, which group has the greatest impact on the yield loss of shallots. There is also no information yet on whether the application of NPK fertilizer can increase the competitiveness of shallots against weeds. For this reason, a study was conducted aiming to determine the dose of NPK fertilizer that increases the competitiveness of the plants in competition with weeds. The research results show that nutsedges significantly dominate in the presence of shallots, both in unfertilized plants and in plants fertilized with NPK Ponska at a dose of 200–400 kg ha-1, with a weighted dominance value of 59.55% – 70.87%. In contrast, the weighted dominance values for grass weeds and broadleaf weeds are 35.82% – 27.46% and 3.93% – 1.43%, respectively. The yield loss in unfertilized shallots with NPK Ponska due to weed competition was 21.57% for nutsedges, 18.96% for grass, and 7.78% for broadleaf weeds, while with fertilization using NPK Ponska at a dose of 200 - 400 kg ha-1, the losses ranged between 22.085% – 28.755%, 11.37% – 14.77%, and 3.404% – 3.711%, respectively. Shallots that were kept weed-free during their growth and fertilized with NPK Ponska 400 kg ha-1 achieved the highest yield of fresh table onions compared to other treatments, namely 400.94 g m-2, at an ideal population density of 64 clumps m-2. The lowest yield was observed in plants that had weeds during their growth and were also fertilized with NPK Ponska 400 kg ha-1, with 76.19 g m-2 at a population density of 20.33 clumps m-2